LETTERS. - Montgomery, Warren; Hayes-Roth, Rick; Hong-Lok Li; Dorfman, Merlin; Quirt, Alan; Kaia. Olsen (Computer (00189162), 2008)
Letters to the editor are presented responding to the articles "Long John Silver and the Digital Jolly Roger" written by David Alan Grier for the March, 2008 issue, "Making a Difference in the Software Century" written by Barry Boehm for the March, 2008 issue, and "Thinking Locally, Acting Globally" written by David Alan Grier for the April, 2008 issue of this magazine.